Surgical management of hydatid Bilio-bronchial fistula by exclusive thoracotomy. (May 2017) - Rabiou, Sani; Lakranbi, Marouane; Ouadnouni, Yassine; Panaro, Fabrizio; Smahi, Mohamed
Abstract: In the industrialized countries, most of Bilio-bronchial fistula are secondary to hepatobiliary trauma, hepatic resection surgery or in the case of congenital malformation of the biliary tract, Bilio-bronchial fistula is recognized as the complication of a number of infectious pathologies such as hydatidosis and hepatic amoebiasis. Among the causes, the Bilio-bronchial fistula of hydatic origin is by far the most frequent especially in the zones of hydatid endemic as Morocco. It is a serious complication of liver hydatid cysts. The surgical management has long been believed to be difficult, and often associated with a very pejorative prognosis due to the simultaneous attack of the thoracic and abdominal stage through the diaphragm. This tripartite involvement reflects the difficulty of choosing the first approach between the thoracic, abdominal or a combination of both approaches. However, progress, especially in the possibility of carrying out adequate preoperative preparation with the increasing introduction of retrograde endoscopic cholangiography with sphincterotomy, has made possible this exclusive thoracotomy surgery with acceptable outcomes. Highlights: The surgical management of Bilio-bronchial fistula has the reputation of being difficult and often associated with a very pejorative prognosis due to the simultaneous attack of the thoracic and abdominal stage through the diaphragm. This tripartite involvement reflects the difficulty of choosing the first approach between the thoracic, abdominal or combinate approach. Surgery of Bilio-bronchial fistula have a high incidence of postoperative infectious complications. It is important to underline the importance of early diagnosis and management in order to minimize postoperative morbidity and mortality.